ELITE DELIBERATION AS DELIBERATIVE DEMOCRACY: EXPERIENCE OF WALISONGO AND NAHDLATUL ULAMA IN NUSANTARA/INDONESIA - Zamharir, Hari; Djaâ€™far, TB Massa; Lubis, Sahruddin; Sadiyatunnimah, Siti (Universitas Nasional, 2020)
Culture-bound political development has recently been voiced by some political theorists. Wisdom of deliberation in Indonesia seems crucial to making democracy work. Amidst the failures or malpractices of democratic politics in Indonesia during the consecutive regimes in power, deliberative democracy is worth revitalizing. The paper makes an account of the legacy of elite deliberation from Islamic civilization that had been in practice by Walisongo in Nusantara and by a big-mass Islamic organization of NU in contemporary Indonesia in electing NUâ€™s top leader. Theories used in the account include Deliberative Theory of Democracy, and the concept â€œculture-context political developmentâ€. The account employs the qualitative research, with meta-analysis in the analysis method. The finding is that transition to democratic culture among the segments of the Indonesian society has been facilitated by the practice of mechanism of Ahlul Hal Wal Aqd (AHWA) or elite deliberation by Walisongo before the independence of Indonesia, with significant contribution to instituting some form of board of trustees, controlling the king in case of misdeed and at the same time building trust in institutionâ€”trusting the king and the board of trusteesâ€”for the peoples in the respective kingdoms. Contribution also takes place by the practice of NU in electing Rais Amâ€”whereby election of NUâ€™s top leader has been deliberated by a few elites with high integrity and trust.